Experimental Investigation of Pressure Distribution Along Makhool Dam Spillway - Muhanad Mohammed Abbas (Diyala Journal of Engineering Sciences, 2013)
This research is an experimental investigation on the pressure distribution  along the surface of Makhool Dam spillway. The work is carried out as series of tests; these series are on the model as it is designed.  (17) Piezometers are fixed along the spillway surface and (4)discharges are performed on the model. The results indicated that the pressure distribution is reduced with the increase  of the discharge and it is increasing with the decrease of the discharge, and there are two regions of negative pressure; the first at the ogee curve and the second at the end of the  sloping straight line after ogee curve, so the slope of the horizontal surface of spillway can  be reduced or change the ogee formula to prevent the cavitations' problems.